Droplets: Moving Droplets in 3D Using Light (Adv. Mater. 35/2018). Issue 35 (26th August 2018) - Xiao, Yang; Zarghami, Sara; Wagner, Klaudia; Wagner, Pawel; Gordon, Keith C.; Florea, Larisa; Diamond, Dermot; Officer, David L.
Abstract : In article number 1801821, David L. Officer and co‐workers break new ground in fluidic chemical transport by guiding organic droplets containing a photoisomerisable material through water with precision and control using light. The droplets can not only be remotely moved from one point to another in a container, but can also be guided to pick up cargo and transfer it to another site to undergo a chemical reaction.